mainstreaming at Universidad Estatal a Distancia, from its institutional framework (Revista Electrónica Calidad en la Educación Superior, 2020)
This article exposes the starting point of mainstreaming assumed by UNED since the year 2000 and the agreements that around this subject have added to this institutional challenge, which has shaped until the present day the statement of the cross-cutting themes from a theoretical and methodological framework. This is how, thru the documental review technique we proceed to locate and analyze the information that would allow to determine from its beginnings the institutional framework that supports and guides the incorporation of mainstreaming in UNED. This framework enables its implementation; this objective comes from a genuine concern to make visible the actions that have been carried out in this matter or the institutional support that mainstreaming requires to achieve its ultimate goal, to permeate into the professional education and transcend beyond space and time, into professional performance. It is valuable to point out, that one of the main outcomes is that mainstreaming has always being a part of UNED from its foundations and has remained in its strategic, politic and normative framework until present day; it is also important to note, the existence of documents in UNED’s curriculum related that figure as the sole orienting criteria for implementation of the cross-cutting themes (Mainstreaming). The studied documents, for the kind of document they represent, reveal that the theoretical and above all methodological resources proposed are limited in its content.
Keywords: Mainstreaming; cross-cutting themes; higher education